If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r * r = -30 + -11r Multiply r * r r2 = -30 + -11r Solving r2 = -30 + -11r Solving for variable 'r'. Reorder the terms: 30 + 11r + r2 = -30 + -11r + 30 + 11r Reorder the terms: 30 + 11r + r2 = -30 + 30 + -11r + 11r Combine like terms: -30 + 30 = 0 30 + 11r + r2 = 0 + -11r + 11r 30 + 11r + r2 = -11r + 11r Combine like terms: -11r + 11r = 0 30 + 11r + r2 = 0 Factor a trinomial. (6 + r)(5 + r) = 0Subproblem 1
Set the factor '(6 + r)' equal to zero and attempt to solve: Simplifying 6 + r = 0 Solving 6 + r = 0 Move all terms containing r to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + r = 0 + -6 Combine like terms: 6 + -6 = 0 0 + r = 0 + -6 r = 0 + -6 Combine like terms: 0 + -6 = -6 r = -6 Simplifying r = -6Subproblem 2
Set the factor '(5 + r)' equal to zero and attempt to solve: Simplifying 5 + r = 0 Solving 5 + r = 0 Move all terms containing r to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + r = 0 + -5 Combine like terms: 5 + -5 = 0 0 + r = 0 + -5 r = 0 + -5 Combine like terms: 0 + -5 = -5 r = -5 Simplifying r = -5Solution
r = {-6, -5}
| 16s=496 | | 3(3x-2.3)=5x-6.9 | | 8x-4=6x-10 | | (3a-2)(4a+1)=5 | | 9h^2-72h=-119 | | -68=-(m+35) | | -68 = - ( m+ 35) | | 7b-587=21 | | 8t-768-13=45 | | 15n=225 | | (18x^2-x-4)=0 | | -8w-744+93=53 | | 6x=28+20 | | 19x^2-8x-20=0 | | 6x+12y=42 | | 22z+593-24=746 | | 4x^2=36x+9 | | 59-d=61 | | 32/4= | | -18b-16938+-588=-840 | | 8n-752+38=78 | | 9n-900+-24=-60 | | 3a^2-10a-131=-6 | | 19x^2-47x+11=0 | | 10n^2+8=198 | | -88=11w | | -84r=0 | | 7=4+3.14 | | 2(5-4y)=10-4y | | 7=4-3.14 | | 4x^2-14x+19=0 | | 4c=-36 |